On the uniqueness of parameter identification for elastic fixation and a point inertia element - Ahtyamova, Aygul Azamatovna; Ahtyamov, Azamat Mukhtarovich (Computational Continuum Mechanics, 2013)
The problem of identification of two relative stiffness coefficients of springs attached to one of the ends of the Euler-Bernoulli beam and the mass and moment of inertia of load concentrated at this end is studied. It is shown that seven natural frequencies suffice for unique identification of parameters of elastic fixing and weight at the beam end. The problem is solved using the method of additional unknowns. This allows us to determine a correctness set of the problem and to prove that the problem is well-posed in the Tikhonov sense. Formulas of identification and corresponding examples are given.